Combined Metabolomics and Network Pharmacology Analysis Reveal the Effect of Rootstocks on Anthocyanins, Lipids, and Potential Pharmacological Ingredients of Tarroco Blood Orange (Citrus sinensis L. Osbeck) - Lei Yang; Shuang Li; Yang Chen; Min Wang; Jianjun Yu; Wenqin Bai; Lin Hong (Plants, 2024)
The benefits of citrus fruits are strongly associated with their secondary metabolites. In this study, we conducted widely targeted metabolomics analyses to compare the variability of the ingredients in four scion–rootstock combinations. A total of 376 differential metabolites were obtained by a multivariate statistical analysis, and a KEGG pathway analysis showed that the enriched metabolic pathways were mainly related to the biosynthesis of flavonoids as well as lipid metabolism. The anthocyanin-targeted metabolomic features showed that cyanidin 3-O-glucoside, cyanidin 3-O-(6-O-malonyl-beta-D-glucoside), cyanidin 3-O-sophoroside, and cyanidin 3-O-xyloside were the pigments responsible for the red color of Tarocco. A lipid metabolomics analysis revealed that when Tarocco was hetero-grafted with rootstock H, there was an increase in the content of each lipid subclass, accompanied by an increase in the levels of unsaturated fatty acids, including polyunsaturated linoleic and linolenic acids, thus impacting the ratio of unsaturated fatty acids to saturated fatty acids. Additionally, we determined their antioxidant capacity (‘Trifoliate orange’ (Z) > ‘Citrange’ (ZC) > ‘Hongju’ (H) > ‘Ziyang Xiangcheng’ (X)) using in vitro assays. Finally, we utilized a network pharmacology analysis to explore the antioxidant mechanisms and potential pharmacological ingredients; we obtained 26 core targets proteins and 42 core metabolites associated with oxidative damage, providing a basis for future preventive and therapeutic applications of these metabolites.